Macrofaunal Ecology of Sedimented Hydrothermal Vents in the Bransfield Strait, Antarctica - Bell, James B.; Woulds, Clare; Brown, Lee E.; Sweeting, Christopher J.; Reid, William D. K.; Little, Crispin T. S.; Glover, Adrian G. (Frontiers in Marine Science, 2016)
Sedimented hydrothermal vents, where hot, mineral-rich water flows through sediment, are poorly understood globally, both in their distribution and the ecology of individual vent fields. We explored macrofaunal community ecology at a sediment-hosted hydrothermal vent in the Southern Ocean. This is the first such study of these ecosystems outside of the Pacific and the furthest south (62˚S) of any vent system studied. Sedimentary fauna were sampled in four areas of the Bransfield Strait (Southern Ocean), with the aim of contrasting community structure between vent and non-vent sites. Macrofaunal assemblages were clearly distinct between vent and non-vent sites, and diversity, richness and density declined towards maximum hydrothermal activity. This variation is in contrast to observations from similar systems in the Pacific and demonstrates the influence of factors other than chemosynthetic primary productivity in structuring infauna at deep-sea vent communities. Vent endemic fauna had limited abundance and were represented by a single siboglinid species at hydrothermally active areas, meaning that that the majority of local biota were those also found in other areas. Several taxa occupied all sampling stations but there were large differences in their relative abundances, suggesting communities were structured by niche variation rather than dispersal ability.